Analisis tantangan pembelajaran PPKN di sekolah dasar pada era digital: Kajian literatur dan analisis berita Pendidikan - Keysha Putri Rahardian; Zahra Pinkan Septia Rahmawati; Farikha Salma Andini; Nawang Wulan Paringsih (Universitas PGRI Madiun, 2026)
The disruption of digital technology has substantially transformed the governance of primary school learning, including the subject of Pancasila and Civic Education (PPKn). This phe nomenon not only offers accelerated access to information and stimulates interactive classroom dynamics, but also entails logical consequences in the form of emerging challenges, such as stu dents' low digital literacy, risks of cyber behavioral deviations, limited teacher technological com petence, and the essential need for moral strengthening. Given this reality, this research is designed to deeply examine various instructional barriers to PPKn at the primary school level in the cyber era through a literature review and an analysis of educational news. Utilizing a qualitative approach based on library research, data were selectively gathered from three representative scientific arti cles and three educational media releases, which were subsequently examined using content analy sis methods. The research findings indicate that the core problems in PPKn pedagogy lie in the stu dents' lack of digital literacy, uneven teacher technological capabilities, limited curriculum support facilities, and the pressing urgency of synergy between schools and parents in fostering children's character. Consequently, PPKn learning scenarios require a more innovative reorientation through the prudent utilization of digital tools, critical reinforcement of information literacy, and the inte gration of national values to ensure that students can function as smart, accountable digital citizens anchored in the axiology of Pancasila.